Computer organization and design : the hardware/software interface - Patterson, David A.; Hennessy, John L. (2014)
"Presents the fundamentals of hardware technologies, assembly language, computer arithmetic, pipelining, memory hierarchies and I/O"--Provided by publisher.
Computer abstractions and technology -- Instructions : language of the computer -- Arithmetic for computers -- The processor -- Large and fast : exploiting memory hierarchy -- Parallel processors from client to cloud.
Previous edition: 2012.
Rev. ed. of: Computer organization and design/John L. Hennessy, David A. Patterson. 1998.
Includes bibliographical references and index.
CSE
STS International
Keywords: Computer organization; System design -- Data processing; Computer architecture; Computer science